Income based price subsidies and parallel imports - Rajat Acharyya; María D. C. García-Alonso (University of Kent, School of Economics, 2010)
We present a policy game where a Rich country has a higher capacity than a Poor country to commit to certain elements of health policy such as providing income related price subsidies and allowing parallel imports (PI). When allowing PI is not a choice for the Poor country, the Rich country allows PI and both countries provide a subsidy to their poorer buyers as the subgame perfect equilibrium policies. However, when the Poor is able to PI a different equilibrium may arise. We show that the ability of the Poor to allow PI might increase welfare in this country even if it is never implemented. We also prove that as the Poor country gets richer, it will not be in their best interest to sign an agreement with the Rich to commit to not allowing PI.
Keywords: D4; L1; I1; 330; income based price subsidies; parallel imports; pharmaceuticals